Effectiveness of vertical subsurface wetlands for iron and manganese removal from wastewater in drinking water treatment plants - Jenny Vanessa Marín-Rivera, , Jader Martínez-Girón, Mauricio Quintero-Angel (Universitas Scientiarum)
Population growth and urbanization pose a greater pressure for the treatment of drinking water. Additionally, different treatment units, such as decanters and filters, accumulate high concentrations of iron (Fe) and manganese (Mn), which in many cases can be discharged into the environment without any treatment when maintenance is performed. Therefore, this paper evaluates the effectiveness of vertical subsurface wetlands for Fe and Mn removal from wastewater in drinking water treatment plants, taking a pilot scale wetland with an ascending gravel bed with two types of plants: C. esculenta and P. australis in El Hormiguero (Cali, Colombia), as an example. The pilot system had three upstream vertical wetlands, two of them planted and the third one without a plant used as a control. The wetlands were arranged in parallel and each formed by three gravel beds of different diameter. The results showed no significant difference for the percentage of removal in the three wetlands for turbidity (98 %), Fe (90 %), dissolved Fe (97 %) and Mn (98 %). The dissolved oxygen presented a significant difference between the planted wetlands and the control. C. esculenta had the highest concentration of Fe in the root with (103.5 ± 20.8) µg/g; while P. australis had the highest average of Fe concentrations in leaves and stem with (45.7 ± 24) µg/g and (41.4 ± 9.1) µg/g, respectively. It is concluded that subsurface wetlands can be an interesting alternative for wastewater treatment in the maintenance of drinking water treatment plants. However, more research is needed for the use of vegetation or some technologies for the removal or reduction of the pollutant load in wetlands, since each drinking water treatment plant will require a treatment system for wastewater, which in turn requires a wastewater treatment system as well